Adipocyte-derived relaxing factor—a fat load to be learnt. (25th February 2022) - Harky, Amer; Chan, Jeffrey Shi Kai; Hui, Jeremy Man Ho; Soppa, Gopal
Abstract : Properties of the radial artery (RA) have been of immense interest to both laboratory scientists and clinicians, especially due to the increasing utilization of RA as a second-choice conduit for coronary artery bypass graft (CABG), after left internal mammary artery.